The Efficacy of a Lifestyle Modification in Pain Management for Arthralgia Patients - Mr. Rameshchandra B. Kaila (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2022)
Arthralgia may result from a variety of reasons. In the majority of instances, joint discomfort is not life-threatening and may be treated at home with over-the-counter drugs and a warm bath. Combining pharmaceutical and non-pharmacological treatments gives the greatest potential for therapeutic success, however establishing the efficacy of such complex therapies remains challenging. The present paper aims to observe various life style modification techniques to treat arthralgia-related pain. It seeks to comprehend the effectiveness of lifestyle adjustment in reducing pain. This study classifies several pain states linked with arthralgia and examines how an understanding of lifestyle may help in reducing pain. Although a comprehensive and systematic examination of individual therapies is outside the scope of this study, it provides reviews of several methods and techniques suggested and recommended by the experts.